Rozważania wstępne o paradygmacie relacyjnym w edukacji i rehabilitacji osób z niepełnosprawnością intelektualną - Kopeć, Danuta (Studia Edukacyjne, 2019)
Polish education and rehabilitation of persons with intellectual disabilities very often neglects the most crucial aspect of being with them, i.e. relationship. The emancipation processes taking place in Polish education and rehabilitation of people with intellectual disabilities have contributed to the gradual emergence of the relational paradigm, the theoretical basis of which constitute the theory of attachment, theory of intersubjectivity and mentalization. The article will attempt to conceptualize the relational paradigm in the field of education and rehabilitation of people with intellectual disabilities. Subsequently, it will present the concepts essential for the relational paradigm: the conceptual apparatus, theories providing its theoretical basis (attachment theory, theory of intersubjectivity). The article will conclude with a preliminary attempt to conceptualize the relational paradigm.